2005
DOI: 10.1099/mic.0.28057-0
|View full text |Cite
|
Sign up to set email alerts
|

Conserved indels in essential proteins that are distinctive characteristics of Chlamydiales and provide novel means for their identification

Abstract: All known chlamydiae are either proven human or animal pathogens or possess such potential. Due to increasing reports of chlamydiae diversity in the environment, it is important to develop reliable means for identifying and characterizing Chlamydiales species. The identification of environmental chlamydiae at present relies on their branching pattern in 16S rRNA trees, as well as 16S/23S consensus motifs which display variability. At present, no reliable molecular signatures are known which are unique to all C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…The presence of these Clostridium-specific signatures in these species would provide a strong case for their transfer to the genus Clostridium. Because all of the conserved indels described here are found in highly conserved regions, it should be possible to obtain sequence information for these signatures from other species by using degenerate PCR primers flanking the indel-containing regions, as described in our other work (Griffiths et al, 2005;Gao & Gupta, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these Clostridium-specific signatures in these species would provide a strong case for their transfer to the genus Clostridium. Because all of the conserved indels described here are found in highly conserved regions, it should be possible to obtain sequence information for these signatures from other species by using degenerate PCR primers flanking the indel-containing regions, as described in our other work (Griffiths et al, 2005;Gao & Gupta, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…indels or signature sequences) in gene/protein sequences that are uniquely shared by particular groups of species provide valuable markers for taxonomic and evolutionary studies (Gupta & Griffiths, 2006). We recently described a number of conserved indels in proteins such as RpoA, EFTu, EF-P, gyrase B and LysRS, that based upon the available information were distinctive characteristics of the Chlamydiales species (Griffiths et al, 2005). Due to lack of sequence information, the presence of these signatures in Verrucomicrobium was not determined.…”
Section: Conserved Inserts In Lysrs and Rpob Proteins That Are Uniquementioning
confidence: 99%
“…indels) in protein sequences provides a powerful tool for evolutionary relationships among distantly related groups (Gupta & Griffiths, 2006). In earlier work, we have described many conserved indels in protein sequences that are either specific for the chlamydiae species or provide information regarding their branching relative to other bacterial phyla (Griffiths & Gupta, 2001;Griffiths et al, 2005;Gupta & Griffiths, 2006). In this work, we have examined the evolutionary relationships among chlamydiae, Verrucomicrobia and Planctomycetes by traditional phylogenetic methods as well as by identifying conserved indels in protein sequences that are uniquely shared by species from these groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it is important to know that new environmental Chlamydia species are steadily described. 8,9 There is ample evidence for a huge diversity and wide distribution of Chlamydiae in nature-and we are exposed to that diversity of species. For example, until recently the recovery of a novel environmental Chlamydia strain from activated sludge by cocultivation with Acanthamoeba species was reported, 8 and it was shown that it is also able to invade mammalian cells.…”
mentioning
confidence: 99%